2008
DOI: 10.1097/aln.0b013e31817f5b73
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Technique for Radical Prostatectomy Surgery Affects Cancer Recurrence

Abstract: Open prostatectomy surgery with general anesthesia, substituting epidural analgesia for postoperative opioids, was associated with substantially less risk of biochemical cancer recurrence. Prospective randomized trials to evaluate this association seem warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
365
7
25

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(410 citation statements)
references
References 46 publications
13
365
7
25
Order By: Relevance
“…An alternative explanation for the difference between our result and that observed by Biki et al 13 (the retrospective study which found that the use of epidural anesthesia conferred a significant survival advantage in prostatectomy) is the relative absence of selection bias in our study. Despite every effort on their part to correct for confounding factors, they would have been unable to correct for biases that were not recorded or were unknown.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation for the difference between our result and that observed by Biki et al 13 (the retrospective study which found that the use of epidural anesthesia conferred a significant survival advantage in prostatectomy) is the relative absence of selection bias in our study. Despite every effort on their part to correct for confounding factors, they would have been unable to correct for biases that were not recorded or were unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…12 Most recently, an analysis of 225 men who underwent open radical prostatectomy for cancer demonstrated a significant association between the use of epidural anesthesia and disease-free survival (hazard ratio for epidural group 0.43) after correcting for a number of known risk factors for recurrence. 13 The authors of these studies all recognized the potential drawbacks of using retrospective data for this purpose and argued that randomized trials should be conducted. Such trials are underway but far from completion.…”
Section: Résumémentioning
confidence: 99%
“…9,10 These findings may therefore imply an association between anesthetic management and long-term outcome. Although NA may reduce the number of postoperative complications and improve short-term mortality in patients undergoing TJR, it remains unknown whether it may also influence long-term survival in these patients.…”
Section: Résumémentioning
confidence: 91%
“…Nous avons créé deux sous-groupes appariés par score de propension, chacun incluant un nombre égal de patients ayant subi une AT sous AG ou AN. (8 [7-10] jours contre 8 [6][7][8][9][10] jours; P = 0,024). Conclusions Nos résultats sont en faveur de l'utilisation de l'AN pour les AT de première intention.…”
Section: Résuméunclassified
“…28 (3) Biki et al reported that epidural anesthesia for prostate resection halved recurrence risk. 29 In this issue of the Journal, Tsui et al evaluated biochemical recurrence after prostate cancer resection in 99 patients who were, in the context of a previous study, randomly assigned to general vs epidural anesthesia more than five years ago. 30 Among these patients, 22 were lost to follow-up, leaving 77 patients available for analysis.…”
mentioning
confidence: 99%